2020
DOI: 10.1007/s40620-020-00702-7
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid in CKD: has the jury come to the verdict?

Abstract: Your article is protected by copyright and all rights are held exclusively by Italian Society of Nephrology. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 59 publications
2
36
0
4
Order By: Relevance
“…Uric acid internalization by URAT 1 is necessary for its deleterious and pro-apoptotic effect at the tubular level, and this is confirmed by the protective effect showed by losartan, which reduced TLR4, MCP1 and Nox4 expression [ 74 ]. Taken together with the association between increased serum uric acid levels and the more severe tubular atrophy and vascular damage described in different series of renal biopsy [ 75 , 76 , 77 , 78 , 79 , 80 ], these findings might explain, at least in part, the unfavorable renal outcomes related to hyperuricemia.…”
Section: Renal Damagementioning
confidence: 75%
“…Uric acid internalization by URAT 1 is necessary for its deleterious and pro-apoptotic effect at the tubular level, and this is confirmed by the protective effect showed by losartan, which reduced TLR4, MCP1 and Nox4 expression [ 74 ]. Taken together with the association between increased serum uric acid levels and the more severe tubular atrophy and vascular damage described in different series of renal biopsy [ 75 , 76 , 77 , 78 , 79 , 80 ], these findings might explain, at least in part, the unfavorable renal outcomes related to hyperuricemia.…”
Section: Renal Damagementioning
confidence: 75%
“…While the observed discrepancies in the outcomes of clinical trials on ULT in patients with CKD may indicate that not all patients will receive renal benefits of ULT, the discrepancies may also be due to a number of other factors, such as low sample size, short duration of follow-up, and lack of consistent definitions of CKD across studies as well as heterogeneity in study designs. Although current guidelines for management of CKD do not recommend treatment of hyperuricemia in the absence of a diagnosis of gout [75], there is increasing consensus that there is a direct causal relationship between high levels of serum urate and the development and progression of CKD [42,57]. ULT with a xanthine oxidase inhibitor should be considered as a therapeutic option in patients at high renal risk and/or declining renal function with hyperuricemia with and without deposition, even if additional studies are needed to identify threshold values for treatment and treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have been carried out to investigate the effects of ULT on CKD progression (reviewed in [42,57,58]). While many trials have reported that ULT has a benefit on renal outcomes, others found that ULT provided no benefit [59].…”
Section: Role Of Urate-lowering Therapy In Prevention Of Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…We similarly found that hyperuricemia was an independent risk factor for CKD stage 3 among patients with ASK. However, the issue of whether the treatment of hyperuricemia would change the CKD outcomes is speculative, since it remains controversial whether hyperuricemia is a consequence or a cause (or both) of CKD [33]. Diabetic nephropathy is the most common cause of ESRD globally, and the presence of diabetes increases the risk of CKD, ESRD, and death [34].…”
Section: Discussionmentioning
confidence: 99%